Exposure to deltamethrin leads to gill liver damage, oxidative stress, inflammation, and metabolic disorders of Japanese flounder (Paralichthys olivaceus) - Li, Bingbu; Wang, Guixing; Zheng, Xinyu; Liu, Mingyang; Yang, Yucong; Ren, Yuqin; Zhang, Yitong; Liu, Yufeng; He, Zhongwei; Ren, Jiangong; Wan, Hailong; Cao, Wei; et al. (Frontiers in Toxicology, 2025)
IntroductionDeltamethrin is a pyrethroid insecticide commonly used to kill animal parasites in aquaculture. However, increasing evidence suggests that deltamethrin affects the health of aquatic animals by causing tissue damage and even death.MethodsIn this study, the damage caused by deltamethrin to the gill and liver tissues, as well as its effects on oxidative stress and immune metabolism, were studied in Paralichthys olivaceus.ResultsWe observed a positive correlation between the residual levels of deltamethrin (Del) and the exposure concentrations, with the highest residue detected in the 0.28 μg/L concentration group (0.0684 mg/kg at 7 days). Then, we observed different degrees of damage to the gill and liver tissues of the Paralichthys olivaceus, including swelling, apical fusion, shedding of gill secondary lamellae, liver cell necrosis, and nuclear vacuolization, by observing tissue sections. Lysozyme enzyme activity increased, whereas catalase and alkaline phosphatase enzyme activities decreased. The liver transcriptome results of the control and high-concentration (0.28 μg/L) groups showed that there were 697 differentially expressed genes, including 390 upregulated and 307 downregulated genes. These differentially expressed genes were significantly enriched in oxidation-reduction, ferroptosis, steroid biosynthesis, and apoptosis pathways.DiscussionIn summary, we found that deltamethrin induces oxidative stress and metabolic disorders in P. olivaceus and leads to inflammation. However, the fish body resists such damage through a complex regulatory network. These experimental results provide a theoretical reference for the safe use of deltamethrin in P. olivaceus.